DEVELOPMENT OF READING-COGNITIVE MOTIVATION IN ELEMENTARY GRADES - Madenova Nesibeli Abadbayevna (Galaxy International Interdisciplinary Research Journal, 2023)
This article examines the development of reading-cognitive motivation in elementary grades, focusing on the interplay between cognitive development and reading abilities. It investigates the factors that influence students’ reading motivation and provides practical suggestions for educators and parents to foster a positive reading environment. The study utilizes a mixed-methods approach, combining quantitative assessments and qualitative analysis of student experiences and perceptions.